Pengaruh Jumlah Kunjungan Wisatawan, Lama Tinggal Wisatawan dan Tingkat Hunian Hotel Terhadap Pendapatan Asli Daerah dan Kesejahteraan Masyarakat Pada Kabupaten/Kota di Provinsi Bali - suastika, i gede yoga; Yasa, I Nyoman Mahahendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 7, Juli 2017 (pp. 1157 - 1394), 2017)
Bali Province is a that rely on tourism sector as a source of revenue contribute large enough on local revenue and public welfare. The purpose of this research is to analyze the number of tourist visit, remained tourists, and occupancy rate for hotels to community welfare by regional real income on regency/city in Bali Provinces. This reasearch used secondary data the data time series beginning in 2010 - 2015. Data collection is done through observation on publication of the BPS Bali Provinces and of Tourism Bali Province. Analysis techniques that used path analysis. Based on analysis of the obtained the result that the number of visits tourists and occupancy rate for hotels have had a positive impact and significant on local revenue, while remained tourists no effect on local revenue in districts in bali province. The number of tourist visits, remained tourists, occupancy rate for hotels have had a positive impact and significant in community welfare, while local revenue no effect on the welfare of the community in districts in Bali Province. Local revenue as variable mediation relations the number of tourist visits, remained tourists and occupancy rate for hotels influential in community welfare.
Keywords: Jumlah Kunjungan Wisatawan; Lama Tinggal Wisatawan; Tingkat Hunian Hotel; Pendapatan Asli Daerah; Kesejahteraan Masyarakat